Photodynamic Therapy: Au Nanoclusters and Photosensitizer Dual Loaded Spatiotemporal Controllable Liposomal Nanocomposites Enhance Tumor Photodynamic Therapy Effect by Inhibiting Thioredoxin Reductase (Adv. Healthcare Mater. 7/2017). Issue 7 (April 2017) - Gao, Fuping; Zheng, Weiping; Gao, Liang; Cai, Pengju; Liu, Ru; Wang, Yaling; Yuan, Qing; Zhao, Yuliang; Gao, Xueyun
Abstract : Au nanoclusters and Clorine 6 (Ce6) co‐loaded spatio‐temporal controllable pH‐sensitive liposomal nanocomposites are internalized by tumor cells via endocytosis are described by Fuping Gao, Xueyun Gao, and co‐workers in article number 1601453. Au nanoclusters and Ce6 are burst and quickly released into cytoplasm under the acidic environment of lysosomes. This way, Au nanoclusters effectively inhibit TrxR in cytoplasm, weaken cell protection mechanisms to photodynamic therapy (PDT) and improve the photodynamic induced intracellular reactive oxygen species, ultimately enhance the effect of PDT.